Analysis of horizontal silo pressure distribution by filling method based on experimental data - Aniskin, A.; Moskalova, K.; Vynnykov, Yu.; Soldo, B. (Eurasian Journal of Applied Engineering and Technology (EJAET), 2022)
The work presents an analysis of the results of the fill-in condition influence of particle inclination on horizontal silage pressure. Analyzed data were obtained from experiments on a rectangular silo model with rigid walls in a different fill-in condition. The filler was a composite mixture of sand and flat shell particles (2:1). The analysis of the results concluded that the volume weight of the composite mixture depends on the fill-in method, which affects the horizontal silage pressures. At filling of 0° and 45°, the pressure is slightly different from Jansen's theory (max 19%) which can be neglectable. Horizontal silage pressures are functionally dependent on the filling method (up to 44%), which should definitely be taken into account.